2006
DOI: 10.1016/j.jsgi.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-β Is the Predominant Estrogen Receptor Subtype in Normal Human Synovia

Abstract: In view of our observation that ER beta but not ER alpha is expressed regularly in normal human synovia in high amounts, we propose that estrogen could play a significant role in synovial membrane function in women and men, operating preferably via the ER beta isoform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 34 publications
1
33
0
2
Order By: Relevance
“…Previous studies have identified estrogen receptors on most joint components, including cartilage, bone, ligaments, and synovium 1822 , indicating a regulatory role for estrogen in these tissues. Because cartilage damage is the major radiological and pathological manifestation observed in joint degeneration, several studies have explored the influence of estrogen on cartilage metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified estrogen receptors on most joint components, including cartilage, bone, ligaments, and synovium 1822 , indicating a regulatory role for estrogen in these tissues. Because cartilage damage is the major radiological and pathological manifestation observed in joint degeneration, several studies have explored the influence of estrogen on cartilage metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In articular tissues, both ER types are expressed by the chondrocytes [10], subchondral bone cells [11], synoviocytes [12], ligament fibroblasts [13] and myoblasts [14] in humans and other species. However, ERα is predominant in cortical bone and ERβ predominates in cartilage, cancellous bone and synovium [10,12,68].…”
Section: Mechanisms Underlying the Effects Of Estrogen On Joint Tissuesmentioning
confidence: 99%
“…Abundant expression of ERβ compared with ERα has been reported in synovial membrane. 31 The existence of two subtypes of ER expression provides one line of evidence that cartilage and synovium are indeed sensitive to estrogens. Chondrocytes are known to endogenously produce estradiol (E2) and it is also known that locally produced E2 stimulates chondrocyte proliferation and confers protection against spontaneous apoptosis.…”
Section: Osteoporosis and Fracturesmentioning
confidence: 99%